Modifikasi Sintesis Membran Nilon-Arang Untuk Pengolahan Air Limbah Batik - Engel Dyta (Fakultas Matematka dan Ilmu Pengetahuan Alam, 2024)
The environmental crisis affecting water bodies, particularly due to waste from the batik industry using synthetic dyes, necessitates effective treatment methods. This study examines the performance of using modified membranes for the treatment of textile effluents. Nylon was used as the polymeric membrane material, and it was incorporated with activated carbon. The variations in the composition of the nylon-carbon membrane were 100%:0%, 90%:10%, 80%:20%, 70%:30%, and 60%:40%. The membrane performance was evaluated to determine the optimal composition of nylon and activated carbon for flux measurement and the removal of Zn, COD, and TSS from textile wastewater. The results indicated that all filtrations exhibited similar permeate flux behavior, with a rapid decline in flux at the initial filtration, followed by a gradual decrease, and eventually reaching a stable flux. The Zn rejection during the filtration of textile wastewater reached 90,55%. Additionally, the removal of chemical oxygen demand (COD) and total suspended solids (TSS) reached 64,44% and 59,36%, respectively.
Reuploud Repository Hasyim Mei 2026 Validasi dan Finalisasi oleh Ratna 15 Juni 2026
Keywords: COD; flux; Nylon-carbon membrane; rejection of Zn; TSS